Synthesis and Structural Characteristics of Semi-Synthetic Biopolymer Blends Based on Polyvinyl Alcohol, Starch and Chitosan - Elshahawy, Amal Gad; Badr, S. I.; Shadi, A. A. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Structural and optical studies in combination with surface morphology investigations were accomplished for blend sample (70/30)wt% PVA/Starch in addition to other samples of the same composition containing added pre-calculated chitosan contents via ordinary casting route. All synthesized samples were tested using various experimental techniques including Fourier transform infrared FT-IR, UV-visible spectroscopic measurements and scanning electron microscopic (SEM). Variations in FT-IR, UV/vis. band positions and intensities were used as an evidence for the interaction between constituent partner polymeric matrices. The X-ray diffraction (XRD) experimental data reveled that introduction of chitosan into the polymeric matrices results in a decreasing of percent crystallinity through material. SEM micrographs for samples containing chitosan different concentration revealed small granules and bright spots that attributed to starch. Adding up to 80% more chitosan caused the cryo-fractured surface to become rougher and more brittle.